Backbone chemical shift assignment of macrophage infectivity potentiator virulence factor of Trypanosoma cruzi - Lopez, J.M.; Antiparra, R.; Lippens, G.; Zimic, M.; Sheen, P.; Maruenda, H. (Springer Netherlands, 2019)
Chagas disease is a trypanosomiasis disease inflicted by Trypanosoma cruzi parasite. In Latin America, at least 10 million people are infected and annually, 10,000 casualties are deplored. Macrophage infectivity potentiator protein is one of the major virulence factors secreted by T. cruzi (TcMIP) in order to infect its host but little is known about its mechanism of action. Studies confer TcMIP an important role in the extracellular matrix transmigration and basal lamina penetration. Here, we report the backbone 1H, 13C, and 15N resonance assignment of TcMIP and the comparison of the secondary structure obtained against reported X-ray crystallography data.
Keywords: Macrophage infectivity potentiator; TcMIP; Virulence factor; NMR resonance assignment; Trypanosoma cruzi; Prolyl cis trans isomerase; FK506 binding protein; FKBP-like protein; https://purl.org/pe-repo/ocde/ford#1.06.03